Conceptual approaches to formation preschool educational institutions‟ future educators art nature creative skills - Maryna Baditsa (Vasyl Stefanyk Precarpathian National University, 2017)
The article deals with the conceptual framework of the process of formation preschooleducational institutions' future educators' art nature creative skills. The author theoreticallygrounded nature of the system, person-activity, and cultural competency approaches asscientific and methodological basis of experimental research program. Key words: conceptual approaches and art nature creative skills, professional training,system, creativity, culture, competence.